The Influence of Accountability, Transparency, Community Participation and the Village Financial System on the Effectiveness of Village Fund Management - Sakdiyah, Lisa Robiatu; Rani, Utpala; Bharata, Risma Wira (Institut Bisnis dan Informatika Kesatuan, 2023)
The purpose of this study is to determine the effect of Accountability, Transparency, Community Participation, and the Village Financial System (Empirical Study in Villages throughout Bangsri Subdistrict). The data in this study are primary data obtained from distributing questionnaires using a Likert measurement scale. The sample of this study was 12 villages in Bangsri subdistrict with 107 respondents. The sampling technique was carried out by purposive sampling method with the criteria that village officials in Bangsri Subdistrict who were directly involved in managing village funds and had at least 1 year of working experience. Data analysis using Multiple Linear Regression analysis. The results of this study indicate that accountability has no effect on the effectiveness of village fund management, transparency has a positive effect on the effectiveness of village fund management, community participation has a positive effect on the effectiveness of village fund management, and the village financial system has a positive effect on the effectiveness of village fund management in Bangsri Subdistrict, Jepara Regency.